Digital competence frameworks in teacher education-A literature review - Aigul Rakisheva (Issues and Trends in Learning Technologies, 2023)
For the quality training of future teachers, it is necessary to have a clear action plan, benchmarks, metrics, and progress indications for using technologies in education. Pre-service teachers' digital competence frameworks can guide their preparation and develop sufficient digital competence before actual practice. This paper analyzes the relevant literature that presents the available ICT competence frameworks for educators. The literature review findings indicate a need for an empirically validated pre-service teachers' digital competence framework that can be adjustable to the context and guide initial teacher preparation in developing modern pre-service teachers' digital competence. The paper also provides information and recommendations to those involved in initial teacher training development, research, and the integration of technologies into pre-service teacher education.